Next Generation Sequencing for Detecting Somatic FAS Mutations in Patients With Autoimmune Lymphoproliferative Syndrome - López-Nevado, Marta; Docampo-Cordeiro, Jorge; Ramos, José T.; Rodríguez-Pena, Rebeca; Gil-López, Celia; Sánchez-Ramón, Silvia; Gil-Herrera, Juana; Díaz-Madroñero, María J.; Delgado-Martín, María A.; Morales-Pérez, Pablo; Paz-Artal, Estela; Magerus, Aude; et al. (Frontiers in Immunology, 2021)
Autoimmune lymphoproliferative syndrome (ALPS) is a primary immune regulatory disorder clinically defined by chronic and benign lymphoproliferation, autoimmunity and an increased risk of lymphoma due to a genetic defect in the FAS-FASL apoptotic pathway. Genetic defects associated with ALPS are germinal and somatic mutations in FAS gene, in addition to germinal mutations in FASLG, FADD, CASP8 and CASP10 genes. The accumulation of CD3+TCRαβ+CD4-CD8- double negative T-cells (DNT) is a hallmark of the disease and 20-25% of ALPS patients show heterozygous somatic mutations restricted to DNT in the FAS gene (ALPS-sFAS patients). Nowadays, somatic mutations in the FAS gene are detected through Sanger sequencing in isolated DNT. In this study, we report an ALPS-sFAS patient fulfilling clinical and laboratory ALPS criteria, who was diagnosed through NGS with a targeted gene panel using DNA from whole blood. Data analysis was carried out with Torrent Suite Software and variant detection was performed by both germinal and somatic variant caller plugin. The somatic variant caller correctly detected other six ALPS-sFAS patients previously diagnosed in the authors’ laboratories. In summary, this approach allows the detection of both germline and somatic mutations related to ALPS by NGS, avoiding the isolation of DNT as the first step. The reads of the somatic variants could be detected even in patients with DNT in the cut off limit. Thus, custom-designed NGS panel testing may be a faster and more reliable method for the diagnosis of new ALPS patients, including those with somatic FAS mutations (ALPS-sFAS).